2001
DOI: 10.1002/ijc.1407
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine angiogenic loop between head-and-neck squamous-cell carcinomas and macrophages

Abstract: Angiogenesis, an essential step in the development of neoplasia, is a complex process that involves the interaction of tumor cells with stromal cells. Tumor-associated macrophages (TAMs) can participate in the induction of tumor angiogenesis and are thought to be of prognostic value in some neoplasms. We have investigated how macrophages contribute to angiogenesis in head-and-neck squamous-cell carcinoma (HNSCC) and have found that tumor cells attract monocytes and activate them to secrete angiogenic factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
1
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 26 publications
4
93
1
4
Order By: Relevance
“…Nesbit et al 38 showed that macrophages activated by MCP-1 release TNF-␣, which may induce angiogenesis in melanoma. Liss et al 39 reported that monocytes/macrophages are recruited and activated by tumor derived MCP-1 and TGF-␤1 and that activated macrophages produce TNF-␣ and IL-1␣, which in turn stimulate tumor cells to produce VEGF and IL-8. MCP-1 also influences angiogenesis directly.…”
Section: Discussionmentioning
confidence: 99%
“…Nesbit et al 38 showed that macrophages activated by MCP-1 release TNF-␣, which may induce angiogenesis in melanoma. Liss et al 39 reported that monocytes/macrophages are recruited and activated by tumor derived MCP-1 and TGF-␤1 and that activated macrophages produce TNF-␣ and IL-1␣, which in turn stimulate tumor cells to produce VEGF and IL-8. MCP-1 also influences angiogenesis directly.…”
Section: Discussionmentioning
confidence: 99%
“…Vol. 63,2006 Review Article 459 plastic cells, tumoral fibroblasts and smooth muscle cells produce distinct monocyte-attracting factors, including monocyte chemoattractant protein-1 (MCP-1), colonystimulating factor-1 (CSF-1), granulocyte-colony stimulating factor (G-CSF), VEGF-A, PlGF and VEGF-C [198][199][200]. Upon invasion into the tumor tissue, monocytes differentiate into macrophages and are specifically activated or de-activated, depending on the cytokine milieu encountered.…”
Section: Tumor-associated Macrophagesmentioning
confidence: 99%
“…In addition, paracrine interactions have been demonstrated between squamous carcinoma cells and other cell types found in stroma. Liss et al (2001) found tumour-derived TGF-b1 and monocyte chemotactic protein-1 attracted and activated monocytes. They suggested that macrophages secreted TNF-alpha and IL-1, which in turn stimulated tumour cells to produce IL-8 and VEGF, the latter cytokine then inducing angiogenesis.…”
mentioning
confidence: 98%